Effectiveness of decentralized distribution of co-designed farmers’ handbook based on farmer-led innovation in a conflict situation: A Case Study from North Shewa zone, Amhara Region. - Getahun, Elizabeth; Habermann, Birgit; Worku, Tigist (International Livestock Research Institute, 2025)
Farmer-led innovation supports farming communities, especially where formal agricultural services are unavailable, limited, or disrupted by conflict. This study explored the effectiveness of decentralized distribution of a farmer handbook, developed by farmers, extension workers, and researchers, in conflict-affected areas of Northern Ethiopia. The study combined qualitative and quantitative research methods. A randomized phone survey was conducted with 71 farmers who received a handbook on feed management for sheep fattening in adaptation to climate change, and interviews with 6 livestock extension workers involved in distribution. Among the 71 respondents, 57 farmers read the material. Farmers found the content, size, and illustrations effective and easy to understand. 54 confirmed that the handbook improved their farming knowledge, and 22 shared the information. The study concluded that disseminating the handbooks through indirect means in conflict situations proved effective. Pretesting the handbook with farmers and agreement on content and design positively impacted reception.